A new surgical technique for scleral fixation using a “knot ball” for scleral-fixated intraocular lenses: impact on clinical outcomes - Mete,Alper (2018)
ABSTRACT Purpose: Scleral fixation surgery is a pivotal procedure that depends on the availability of robust and innovative surgical fixation methods. There continues to be a need for innovation in suture fixation techniques, particularly for intraocular lens implantation. Methods: We conceived and designed a “knot ball” scleral fixation technique for suture burial in a retrospective sample of 108 patients with primary (n=40) or secondary (n=68) scleral-fixated intraocular lens. Importantly, our technique did not require additional scleral flap or tunnel procedures. We evaluated pre- and postoperative best-corrected visual aquity (BCVA) and postoperative complications. All data were analyzed and compared between groups. Results: The preoperative mean BCVA improved significantly in both groups using the “knot ball” fixation technique (p<0.01). The extent of the improvement in the best-corrected visual acuity and late complications one month post-surgery were not significantly different between the groups (p>0.05). These clinical outcomes were consistent with those described in the ophthalmology literature. Conclusion: A “knot ball” scleral fixation technique is reported; to the best of our knowledge, this is the first report of such a technique, which offers a less invasive and simplified surgical procedure for transscleral fixation of scleral-fixated intraocular lenses. Moreover, the technique appears to display similar effectiveness and safety compared with existing scleral fixation techniques. We suggest that the “knot ball” technique warrants further research focus and clinical evaluation in future studies.